(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive analysis of theoretical grammar as a central field of linguistics concerned with the internal structure and systematic organization of language. The study explores the fundamental components of theoretical grammar, including morphology, syntax, semantics, and phonology, offering detailed explanations and illustrative examples for each. Special attention is given to how these components interact to form a coherent linguistic system. Furthermore, the article examines the role of theoretical grammar in identifying universal patterns across languages and its contribution to modern linguistic theories such as generative, functional, and cognitive grammar. The practical applications of theoretical grammar are also discussed, particularly in the areas of language teaching, translation, and computational linguistics. The purpose of this article is to demonstrate that language is not a random collection of words, but a structured and rule-governed system shaped by deep underlying principles.